MODEL CASH BACK JUAL BELI PAKET LEBARAN PERSPEKTIF EKONOMI SYARIAH - E. Mulya Syamsul; Abu Syhabudin; Juwita, Wullan (ITB AAS INDONESIA Surakarta, 2025)
This study examines the mechanism and consumer perception of the Ceria Eid Savings Package program conducted by a business owner in Village Cigasong. The program offers basic needs and children’s gift packages (My Baby) that can be paid daily over a 300-day period, with a cashback incentive as an added appeal. The research method used is interviews with three sources: the business owner (Mrs. Lina Marlina) and two consumers (Mrs. Eni Rohaeni and Mrs. Titing). The findings indicate that while some consumers feel helped by the program due to reduced Eid expenses and cashback benefits, others express concerns regarding package transparency, potential misuse of funds, and the risk of price increases closer to Eid. Therefore, transparency, clear legality, and proper oversight are required to build trust and ensure the sustainability of such a savings scheme.